Effects of polycrystalline AlN film on the dynamic performance of AlGaN/GaN high electron mobility transistors. (15th June 2018) - Zhang, Dongliang; Cheng, Xinhong; Zheng, Li; Shen, Lingyan; Wang, Qian; Gu, Ziyue; Qian, Ru; Wu, Dengpeng; Zhou, Wen; Cao, Duo; Yu, Yuehui
Abstract: During the fabrication process of AlGaN/GaN HEMTs, SiNx films grown by plasma enhanced chemical vapor deposition (PECVD) are usually utilized to passivate AlGaN/GaN surface. However, PECVD with high energy of plasma would induce the surface damage. Plasma in plasma enhanced atom layer deposition (PEALD) process is gentle and remote. Consequently, AlN films grown by PEALD are explored as passivation layer on AlGaN/GaN surface. In comparison with PECVD SiNx, AlN film grown by PEALD, accompanied with 850 °C rapid temperature annealing (RTA), can improve 2DEG mobility 16.4%, the peak transconductance 38.6%, saturation drain current 26.3%, reduce static on-resistance 19.2%, and dynamic on-resistance only increased 14% after 50 V off-state stress and 200 μs recovering time. The annealing process at 850 °C changed AlN film polycrystalline structure and generated positive polarization charges of 3.6 × 10 12  cm −2 at AlN/GaN heterojunction, which compensated the deep-level trap charging effect, and suppressed current collapse and increase of dynamic on-resistance. Highlights: 4 nm polycrystalline AlN film was formed after annealing the film at 850 °C for 60 s in nitrogen ambient. Large density of positive polarization charges exists in the polycrystalline AlN film. Polycrystalline AlN film can effectively improve the DC performance and suppress the degradation of dynamic on-resistance. Graphical abstract: